Thresholds: Rethinking Spirituality Through Music - Cobussen, Marcel -1962 (Aldershot Ashgate, 2008)
In Thresholds, Marcel Cobussen rethinks the relationship between music and spirituality. The book presents an idea of spirituality in and through music that counters strategies of exclusion and mastering of alterity and connects it to wandering, erring, and roving. Cobussen regards spirituality as a (non)concept that escapes categorization, classification, and linguistic descriptions. Spirituality is a-topological, non-discursive and a manifestation of 'otherness'. And it is precisely music (or better: listening to music) that induces these thoughts. By carefully encountering, analysing, and evaluating certain examples from classical, jazz, pop and world music it is possible to detach spirituality from concepts of otherworldliness and transcendentalism.
Keywords: Music philosophy and esthetics